Գրիգոր Մագիստրոսի «Յաղագս կրօնաւօրի ումեմն, զոր Շապուհ անուանեն» թուղթը - Հովսեփյան, Հասմիկ
В результате исследования обсуждаемого текста мы определили четкий источник, к которому автор подошел творчески. Чтобы понять и проанализировать сложное сочинение Григора Магистроса, мы рассмотрели его творческие особенности, подчеркнув структурные и языковые характеристики. Помимо труднодоступности, с лингвистической и стилистической точек зрения, примечательно использование согласных, которые преобладают во всех частях стихотворного слога. Так, в первых четырех строках повторяется буква կ, в строках с пятой по седьмую — տ, в строках с восьмой по одиннадцатую — բ, в последних четырех строках — ն. Мы перевели текст на современный aрмянский язык, основываясь на двух томах ―Нового словаря армянского языка‖, а также на книгах ―Учебный словарь армянского языка‖, а с точки зрения его понимания, обращая внимание на разночтения, имеющие определенные отличия с критическим текстом. As a result of the study of the text under discussion, we identified a source to which the author approached creatively. In order to understand and analyze the complex work of Grigor Magistros, we examined its creative features, highlighting structural and linguistic characteristics. In addition to the difficulty of access, from the linguistic and stylistic points of view, the use of consonants, which prevails in all parts of the poetic word, is noteworthy. Thus, the letter կ is repeated in the first four lines, տ in the fifth to seventh lines, բ in the eighth to eleventh lines, and ն in the last four lines. We have translated the text into modern Armenian language, basing uрon two volumes of the "New Dictionary of the Armenian Language", as well as on the books of "Manual Dictionary of the Armenian Language", and paying attention, from the point of view of understanding it, to the readings that present certain differences with the critical text.
Keywords: Գրականություն